2003
DOI: 10.1023/a:1024065015717
|View full text |Cite
|
Sign up to set email alerts
|

Juveniles' competence to stand trial: A comparison of adolescents' and adults' capacities as trial defendants.

Abstract: Abilities associated with adjudicative competence were assessed among 927 adolescents in juvenile detention facilities and community settings. Adolescents' abilities were compared to those of 466 young adults in jails and in the community. Participants at 4 locations across the United States completed a standardized measure of abilities relevant for competence to stand trial (the MacArthur Competence Assessment Tool-Criminal Adjudication) as well as a new procedure for assessing psychosocial influences on lega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
273
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 363 publications
(296 citation statements)
references
References 19 publications
15
273
1
4
Order By: Relevance
“…The results of the MacArthur Foundation Research Network's earlier study of age differences in competence to stand trial, which depends on individuals' ability to understand facts about a court proceeding and to reason with those facts in a rational fashion, also were consistent with these findings. We found significant differences between the competence-related abilities of adults and those of adolescents who were 15 and younger, but no differences between the abilities of adults and those of adolescents who were 16 and older (Grisso et al, 2003). This general pattern, indicating that adolescents attain adult levels of competence to stand trial somewhere around age 15, has been reported in similar studies of Jennifer Woolard decision making across a wide variety of domains (e.g., Grisso, 1980;Jacobs-Quadrel, Fischhoff, & Davis, 1993) and in many studies of age differences in individuals' competence to provide informed consent (Belter & Grisso, 1984;Grisso & Vierling, 1978;Gustafson & McNamara, 1987;Weithorn & Campbell, 1982).…”
Section: Elizabeth Cauffmancontrasting
confidence: 56%
See 2 more Smart Citations
“…The results of the MacArthur Foundation Research Network's earlier study of age differences in competence to stand trial, which depends on individuals' ability to understand facts about a court proceeding and to reason with those facts in a rational fashion, also were consistent with these findings. We found significant differences between the competence-related abilities of adults and those of adolescents who were 15 and younger, but no differences between the abilities of adults and those of adolescents who were 16 and older (Grisso et al, 2003). This general pattern, indicating that adolescents attain adult levels of competence to stand trial somewhere around age 15, has been reported in similar studies of Jennifer Woolard decision making across a wide variety of domains (e.g., Grisso, 1980;Jacobs-Quadrel, Fischhoff, & Davis, 1993) and in many studies of age differences in individuals' competence to provide informed consent (Belter & Grisso, 1984;Grisso & Vierling, 1978;Gustafson & McNamara, 1987;Weithorn & Campbell, 1982).…”
Section: Elizabeth Cauffmancontrasting
confidence: 56%
“…As we noted earlier, in addition to the present study, the MacArthur Network also conducted a study of age differences in capacities related to competence to stand trial (Grisso et al, 2003). The main instrument used to assess these capacities was the MacArthur Competence Assessment Tool-Criminal Adjudication (MacCAT-CA), a standardized interview that measures respondents' understanding of and reasoning about their legal situation (Poythress et al, 1999).…”
Section: Figure 1 Psychosocial Maturity (Standardized Composite Scorementioning
confidence: 96%
See 1 more Smart Citation
“…Deficits in psychosocial maturity often are cited as indicia of reduced culpability when young people run afoul of the law (Scott and Steinberg, 2003) . In this framework, law and social rules are externalities to adolescent development.…”
Section: A5mentioning
confidence: 99%
“…Drawing from recent studies on children's behavior toward the law and legal actors, we assume that legal socialization is a critical part of adolescent development that shapes adolescents' attitudes and behaviors in a variety of legal tasks (Flanagan and Sherrod, 1998;Grisso, 2000;Grisso et al, 2003;Steinberg and Cauffman, 1996). This certainly is true among adults, where there is consistent evidence across in studies with diverse populations in a wide range of tasks and settings showing that both moral values and orientations toward legal authority-such as perceived legitimacy-shape two dimensions of adult behavior with respect to the law: compliance and cooperation (Tyler, 1990;Tyler and Huo, 2002).…”
Section: Legal Socializationmentioning
confidence: 99%